Creating and Implementing an Effective and Deterrent National Cyber Security Strategy. (1st June 2020) - Senol, Mustafa; Karacuha, Ertugrul
Abstract : This paper presents a new national cyber security strategy (NCSS) covering the deterrence perspective from creation to implementation. With the aim of responding to and ensuring cyber security effectively, studies on which pathways should be followed and what methods should be used to develop, create, and implement a NCSS are being conducted in Turkey, as in all countries. In this context, by explaining the importance of cyber power, the need for cyber power to be considered as one of the elements of national power and the importance of providing security against cyber attacks with deterrence by cyber power are discussed, while a new and integrated approach for the creation and implementation of a NCSS and an authoritarian organizational structure responsible for this strategy is proposed. It can be concluded that the proposed effective and deterrent NCSS model and approaches might help to efficiently and effectively handle these issues for better management, control, and auditing for cyber security issues; provide new concepts for cyber security issues supported by cyber power and deterrence on this issue in the world; introduce integrated approach to cyber security strategies and policies on the stages of developing and implementing a NCSS; bring a number of issues to support cyber security and defence in different perspectives; and achieve a high degree of success, especially in terms of effectiveness and existing deterrence strategies and action plans of basic structure, with the proposed approach. Finally, it is expected that the proposed strategy, steps, and suggestions might help to improve cyber security issues and national strategies in near future to secure national assessment more than ever with a powerful concept of deterrence. In addition, this approach, which has been put forward for effective implementation of cyber security by ensuring better management, control, and supervision, can be easily used by all other countries.